Software Update: The ORCA Program System—Version 6.0 - Neese, Frank (Wiley interdisciplinary reviews. Computational molecular science, 2025)
ABSTRACT Version 6.0 of the ORCA quantum chemistry program suite was released in July 2024. ORCA 6.0 is a major turning point in the history of the program since it represents a near complete rewrite of the code base that leads to: (1) major performance improvements, (2) a clean and highly efficient code base that greatly facilitates future development, (3) a large amount of new functionality, and (4) new interface capabilities that facilitate inter‐operability with other quantum chemistry program packages. The article describes the most salient features of the program. This article describes the philosophy behind‐ and new features in the ORCA quantum chemistry program suite, version 6.0.